Survey of neonatal resuscitation practices showed post‐training improvements but need to reinforce preterm management, monitoring and adrenaline use. (19th March 2017) - Izquierdo, Montserrat; Iriondo, Martín; Ruiz, César; Zeballos, Gonzalo; Sánchez, Miguel; González, Eva; Vento, Máximo; Thió, Marta; ,
Abstract: Aim: Neonatal resuscitation surveys have showed practice variations between countries, centres and levels of care. We evaluated delivery room practices after a nationwide neonatal resuscitation training programme focused on nontertiary centres. Methods: A 2012 survey sent to all Spanish hospitals handling deliveries covered staff availability and training, equipment and practices in the delivery room and during transfers to neonatal intensive care units. The results from 98 centres that had completed a previous survey in 2007 were analysed by levels of care. Pearson's chi‐square test was used to compare the proportions. Results: The following had significantly improved in 2012 compared to 2007: the availability of T‐piece resuscitators (71.4% vs. 41.8%), plastic wraps (69.4% vs. 31.6%), gas blenders (79.6% vs. 40.8%), pulse oximetry (92.9% vs. 61.2%), use of continuous positive airway pressure (82.7% vs. 43.9%) (all p < 0.01), the availability of instructors (55.6% vs. 83.3%, p < 0.05) and neonatal resuscitation courses (40.8% vs. 79.6%, p < 0.05) in nontertiary centres. In 2012, the use of exhaled carbon dioxide detectors was <7% and endotracheal administration of adrenaline was >90%. Conclusion: Neonatal resuscitation equipment and practices improved over time, but several aspects needed to be reinforced in training programmes, namely preterm infants' management, monitoring and adrenaline administration.